Administrative Knowledge of Sport and Youth Forum Mangers In Baghdad From the Employees’ Point of View - Wahab, Slah; Ali, Jasim (Journal of Physical Education, 2018)
Administrative Knowledge of Sport and Youth Forum Mangers In Baghdad From the Employees’ Point of ViewThe study aims to build a standard of administrative knowledge for the managers of the youth and sports forums in Baghdad and to identify their level from the point of view of the employees. The problem lies in the researcher's attempt to answer a specific question: Do the directors of the youth and sports forums in Baghdad have sufficient administrative knowledge, This vital institution working in the sports field Baghdad? . The researcher followed the descriptive research method in the method of associative relationships on a sample of the continuous employees in the Baghdad governorate for the year 2018 of 608 individuals who were chosen by a vertical percentage of 62.875% of the original society for the period from 14/12/2017 to 5/4. (308), and sample application (298). After a series of logical procedures in constructing measurement tools in sport management according to the measurement parameters The scale of the study was constructed and then applied to the application sample and its results were processed using the pouch system Statistical (SPSS), the researcher concludes that the managers of youth and sports forums need better knowledge of the administrative level.